Relationship between SSN, F107 and Z component of EMF during the 24th Solar Cycle - Canyılmaz, Murat; Guzel, Esat; Yalcın, Emrah (Niyazi BULUT, 2021)
The study inquires the statistical relationship between Solar activity indices SSN, F10.7 and Earth’s Magnetic Field (EMF) Z component which were measured in Iznik Magnetic Observatory, for the 24th Solar Cycle. Pearson, Spearman and Kendall Tau-b correlation analysis were made according to the normality analysis of the values which was determined in accordance with skewness and kurtosis values. Low level of correlations with high significance were found between the variables.
Keywords: Metrology; Applied and Industrial Physics; Metroloji; Uygulamalı ve Endüstriyel Fizik